A meta-analysis of safety and efficacy of regorafenib for refractory metastatic colorectal cancer - Xue, Wu-Song (Medicine (Baltimore), 2018)
BACKGROUND: Patients with metastatic colorectal cancer (mCRC) often suffer from progressive disease despite previous therapy. It has been a great challenge for those patients. In 2012, regorafenib was approved for mCRC. In this meta-analysis, we aimed to collect and present existing data to explorethe clinical use of regorafenib. METHODS: The online electronic databases, such as PubMed, Embase, and the Cochrane library, updated to November 2017 were systematically searched. Trials on the effectiveness of regorafenib in patients who suffer from treatment-refractory metastatic colorectal cancer were included, of which the main outcomes included 3 parameters: overall survival (OS), progression-free survival (PFS), and grade 3/4 AE. RESULTS: Totally, 4 trials were included in this meta-analysis. The OD was significantly better with the use of regorafenib (OR = 0.78, 95%CI = 0.65–0.94, I(2) = 69%, P = .008), and PFS (OR = 0.52, 95%CI = 0.34–0.79, I(2) = 97%, P = .002). However, the most common toxicities occurred more frequently in the regorafenib group than the control group (OR = 3.73, 95%CI = 1.68–8.28, I(2) = 79%, P = .001). CONCLUSION: Regorafenib demonstrates better efficacy and has manageable adverse-event profile for treatment-refractory mCRC. Considering the safety feature of regorafenib, further studies and clinical trials are warranted to investigate the dosing of regorafenib and alternative approaches are needed to explore predictive biomarker fortherapy selection.